Estabilidade da polpa de mangaba (Hancornia speciosa gomes) congelada e armazenada - Gonçalves, Gilma Auxiliadora Santos (2017)
Mangaba (Hancornia speciosa Gomes), a fruit from Brazilian Cerrado (tropical savanna ecoregion), highlight for its high nutritional value and bioactive compounds, as well as attractive and peculiar sensory characteristics of flavor and aroma. As processing may alter its original characteristics, this research aimed to evaluate the effect of processing (pasteurization and freezing methods) and long-term storage on the phenolic profile, bioactive compounds, antioxidant capacity, enzymatic activity, volatile compounds and sensory profile of mangaba pulp. Fruits from Curvelo - MG, Brazil, were selected, washed, sanitized and pulped and packed (100 mL) in LDPE (Low density polyethylene) plastic bags. The pulps were submitted to two levels of pasteurization (pasteurized and unpasteurized), two freezing methods (forced air and static air) and five storage times (zero, 3, 6, 9 and 12 months) for the physical and chemical analyzes, and four times (zero, 4, 8 and 12 months) for microbiological and sensory analyzes. Samples were thawed in tap water. It was concluded that the forced air freezing method is more efficient in the retention of vitamin C, and pasteurization favors greater retention of total phenolics, antioxidant capacity and lower enzymatic activity. Most of the individual phenolic is retained for up to six months, with (+)-catechin and trans-cinnamic acid being the most stable ones. Twenty-five volatile compounds were tentatively identified in the fruit and pulp, with the esters predominating in both. The 4-pentenyl acetate and isopentyl acetate esters were predominant in the fruit, while in the pulps ethanol was predominant after three months of storage. Pasteurization favors retention of aroma compounds from mangaba pulp. Storage from nine months favors the development or accumulation of compounds responsible for aroma degradation such as ethanol, ethyl acetate and acetic acid. Soluble solids content tends to decrease, while pH, titratable acidity and pulp color are poorly altered by pasteurization, freezing and storage. Temporal dominance of sensations (TDS) analysis identified sour taste as dominant in most treatments, combined with the identification of off-flavors in unpasteurized pulps stored for four months. Pasteurization, regardless of the freezing method, promotes greater acceptance of mangaba pulp for up to eight months. Mangaba pulp, even at twelve months of frozen storage, is a good source of bioactive compounds and has good antioxidant capacity and good sensory acceptance.